The Presence of Padmasari Mestikajati as Women Representation on Politics - Tegar Muhammad Rafly; Muhammad Nizar Rohman; Najma Nuraisyah (Politik Indonesia: Indonesian Political Science Review, 2025)
This study aims to analyze Padmasari Mestikajati's work as a representation of women in Indonesian politics, particularly in the context of local politics, which is still characterized by low female representation and strong structural barriers such as patriarchal culture, male elite domination, limited access to political resources, and the placement of female candidates in non-strategic positions. Focusing on Padmasari's campaign strategies and legislative contributions in the Central Java Provincial House of Representatives (DPRD), this study uses descriptive qualitative methods through interviews, observations, and literature studies to examine the dynamics of local politics and gender policies. The results show that Padmasari's success in retaining her legislative seat for two terms was not only influenced by her personal political capital (political kinship and educational background), but also by her ability to optimize adaptive and contextual campaign strategies, as well as the support of the 30% affirmative action quota policy that increased women's representation. Unlike many female politicians who stop at descriptive representation, Padmasari demonstrates substantive representation through the initiation of pro-women policies, particularly the advocacy for the provision of lactation rooms and the strengthening of kindergarten education infrastructure. Thus, this study emphasizes the importance of examining female figures who are not only electorally successful but also capable of transforming representation into concrete policies, thereby contributing theoretically and empirically to the development of studies on women's representation in local politics in Indonesia.